HUBUNGAN PERILAKU MEMBOLOS DENGAN KEMATANGAN EMOSI PESERTA DIDIK KELAS VIII SMP ASSHIDDIQIYAH - Resya Susanty; Teti Sobari; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The purpose of the study was to examine whether there was a relationship between Truancy behavior and emotional maturity in VIII graders of Asshiddiqiyah Middle School. The research method used was a correlational quantitative research method with 52 research samples. The data analysis technique was carried out by the correlational test with the help of SPSS 22. Based on the results of the study through the correlational test, the product moment obtained produced a negative relationship between emotional associated with ditching VIII grade students of Asshiddiqiyah Middle School with marks (2 tailed) of 0,000 and r -0,583 . Higher grades mean higher maturity of students, so it is better for more choices than studentsKeywords: Emotional Maturity, Truancy Behavior.